Multilayer capsules made of weak polyelectrolytes: a review on the preparation, functionalization and applications in drug delivery - Sharma, Varsha; Sundaramurthy, Anandhakumar (Beilstein Journal of Nanotechnology, 2020)
Multilayer capsules have been of great interest for scientists and medical communities in multidisciplinary fields of research, such as drug delivery, sensing, biomedicine, theranostics and gene therapy. The most essential attributes of a drug delivery system are considered to be multi-functionality and stimuli responsiveness against a range of external and internal stimuli. Apart from the highly explored strong polyelectrolytes, weak polyelectrolytes offer great versatility with a highly controllable architecture, unique stimuli responsiveness and easy tuning of the properties for intracellular delivery of cargo. This review describes the progress in the preparation, functionalization and applications of capsules made of weak polyelectrolytes or their combination with biopolymers. The selection of a sacrificial template for capsule formation, the driving forces involved, the encapsulation of a variety of cargo and release based on different internal and external stimuli have also been addressed. We describe recent perspectives and obstacles of weak polyelectrolyte/biopolymer systems in applications such as therapeutics, biosensing, bioimaging, bioreactors, vaccination, tissue engineering and gene delivery. This review gives an emerging outlook on the advantages and unique responsiveness of weak polyelectrolyte based systems that can enable their widespread use in potential applications.
Keywords: drug delivery; functionalization; multilayer capsules; synthesis; weak polyelectrolytes

(untitled) - Kurapati, R.; Groth, T. W.; Raichur, A. M. (ACS Appl. Bio Mater., 2019)

(untitled) - Iler, R. K. (J. Colloid Interface Sci., 1966)

(untitled) - Decher, G.; Hong, J. D. (Ber. Bunsen-Ges., 1991)

(untitled) - Skirtach, A. G.; Yashchenok, A. M.; Möhwald, H. (Chem. Commun., 2011)

(untitled) - Esser-Kahn, A. P.; Odom, S. A.; Sottos, N. R.; White, S. R.; Moore, J. S. (Macromolecules, 2011)

(untitled) - Kharlampieva, E.; Sukhishvili, S. A. (Langmuir, 2003)

(untitled) - Sukhishvili, S. A. (Curr. Opin. Colloid Interface Sci., 2005)

(untitled) - Gil, P. R.; del Mercato, L. L.; del Pino, P.; Muñoz-Javier, A.; Parak, W. J. (Nano Today, 2008)

(untitled) - Sukhorukov, G. B.; Brumen, M.; Donath, E.; Möhwald, H. (J. Phys. Chem. B, 1999)

(untitled) - Sukhorukov, G. B.; Rogach, A. L.; Zebli, B.; Liedl, T.; Skirtach, A. G.; Köhler, K.; Antipov, A. A.; Gaponik, N.; Susha, A. S.; Winterhalter, M.; Parak, W. J. (Small, 2005)

(untitled) - Mora-Huertas, C. E.; Fessi, H.; Elaissari, A. (Int. J. Pharm., 2010)

(untitled) - Gao, C.; Donath, E.; Moya, S.; Dudnik, V.; Möhwald, H. (Eur. Phys. J. E: Soft Matter Biol. Phys., 2001)

(untitled) - Dubreuil, F.; Elsner, N.; Fery, A. (Eur. Phys. J. E: Soft Matter Biol. Phys., 2003)

(untitled) - Dubas, S. T.; Schlenoff, J. B. (Macromolecules, 1999)

(untitled) - Izumrudov, V.; Kharlampieva, E.; Sukhishvili, S. A. (Macromolecules, 2004)

(untitled) - Shiratori, S. S.; Rubner, M. F. (Macromolecules, 2000)

Stimuli Responsive Polymeric Nanocarriers for Drug Delivery Applications - Sundaramurthy, A. (Responsive polyelectrolyte multilayer nanofilms for drug delivery applications, 2018)

(untitled) - Zyuzin, M. V.; Timin, A. S.; Sukhorukov, G. B. (Langmuir, 2019)

(untitled) - Izumrudov, V. A.; Mussabayeva, B. K.; Murzagulova, K. B. (Russ. Chem. Rev., 2018)

(untitled) - Ghiorghita, C.-A.; Bucatariu, F.; Dragan, E. S. (Mater. Sci. Eng., C, 2019)

(untitled) - Rathee, V. S.; Sidky, H.; Sikora, B. J.; Whitmer, J. K. (Polymers (Basel, Switz.), 2019)

(untitled) - De Koker, S.; Hoogenboom, R.; De Geest, B. G. (Chem. Soc. Rev., 2012)

(untitled) - Gao, C.; Moya, S.; Lichtenfeld, H.; Casoli, A.; Fiedler, H.; Donath, E.; Möhwald, H. (Macromol. Mater. Eng., 2001)

(untitled) - Mauser, T.; Déjugnat, C.; Möhwald, H.; Sukhorukov, G. B. (Langmuir, 2006)

(untitled) - Déjugnat, C.; Sukhorukov, G. B. (Langmuir, 2004)

(untitled) - Schuetz, P.; Caruso, F. (Adv. Funct. Mater., 2003)

(untitled) - Caruso, F.; Trau, D.; Möhwald, H.; Renneberg, R. (Langmuir, 2000)

(untitled) - Shenoy, D. B.; Antipov, A. A.; Sukhorukov, G. B.; Möhwald, H. (Biomacromolecules, 2003)

(untitled) - Anandhakumar, S.; Debapriya, M.; Nagaraja, V.; Raichur, A. M. (Mater. Sci. Eng., C, 2010)

Bioactive Surfaces - Volodkin, D.; Skirtach, A.; Möhwald, H. (LbL Films as Reservoirs for Bioactive Molecules, 2010)

(untitled) - Antipov, A. A.; Shchukin, D.; Fedutik, Y.; Petrov, A. I.; Sukhorukov, G. B.; Möhwald, H. (Colloids Surf., A, 2003)

(untitled) - Volodkin, D. V.; Petrov, A. I.; Prevot, M.; Sukhorukov, G. B. (Langmuir, 2004)

(untitled) - Chen, Y. D.; Xu, J. J.; Wang, Y.; Chen, H.; Luo, Q. J.; Li, X. D.; Zhu, W. P. (RSC Adv., 2017)

(untitled) - Sundaramurthy, A.; Sundramoorthy, A. K. (Int. J. Biol. Macromol., 2018)

(untitled) - Li, J.; Jiang, Z.; Wu, H.; Zhang, L.; Long, L.; Jiang, Y. (Soft Matter, 2010)

(untitled) - Chen, L.; An, H. Z.; Doyle, P. S. (Langmuir, 2015)

(untitled) - Tian, Y.; Li, L.; Han, H.; Wang, W.; Wang, Y.; Ye, Z.; Guo, X. (Polymers (Basel, Switz.), 2016)

(untitled) - Kharlampieva, E.; Kozlovskaya, V.; Tyutina, J.; Sukhishvili, S. A. (Macromolecules, 2005)

(untitled) - Wang, Z.; Feng, Z.; Gao, C. (Chem. Mater., 2008)

(untitled) - Joanny, J. F. (Eur. Phys. J. B, 1999)

(untitled) - Lytle, T. K.; Chang, L.-W.; Markiewicz, N.; Perry, S. L.; Sing, C. E. (ACS Cent. Sci., 2019)

(untitled) - Caruso, F.; Lichtenfeld, H.; Donath, E.; Möhwald, H. (Macromolecules, 1999)

(untitled) - Philipp, B.; Dautzenberg, H.; Linow, K.-J.; Kötz, J.; Dawydoff, W. (Prog. Polym. Sci., 1989)

(untitled) - Antipov, A. A.; Sukhorukov, G. B.; Leporatti, S.; Radtchenko, I. L.; Donath, E.; Möhwald, H. (Colloids Surf., A, 2002)

(untitled) - Steitz, R.; Leiner, V.; Tauer, K.; Khrenov, V.; von Klitzing, R. (Appl. Phys. A: Mater. Sci. Process., 2002)

(untitled) - Wang, L.; Wang, Z.; Zhang, X.; Shen, J.; Chi, L.; Fuchs, H. (Macromol. Rapid Commun., 1997)

(untitled) - Zhang, Y.; Guan, Y.; Yang, S.; Xu, J.; Han, C. C. (Adv. Mater. (Weinheim, Ger.), 2003)

(untitled) - Sukhishvili, S. A.; Granick, S. (Macromolecules, 2002)

(untitled) - Kharlampieva, E.; Sukhishvili, S. A. (Polym. Rev. (Philadelphia, PA, U. S.), 2006)

(untitled) - Kozlovskaya, V.; Sukhishvili, S. A. (Macromolecules, 2006)

(untitled) - Kharlampieva, E.; Kozlovskaya, V.; Sukhishvili, S. A. (Adv. Mater. (Weinheim, Ger.), 2009)

(untitled) - Yang, S. Y.; Lee, D.; Cohen, R. E.; Rubner, M. F. (Langmuir, 2004)

(untitled) - Tong, W.; Gao, C.; Möhwald, H. (Macromolecules, 2006)

(untitled) - Bucatariu, F.; Ghiorghita, C.-A.; Dragan, E. S. (Colloids Surf., A, 2018)

(untitled) - Zhang, Y.; Yang, S.; Guan, Y.; Cao, W.; Xu, J. (Macromolecules, 2003)

(untitled) - Feng, Z.; Wang, Z.; Gao, C.; Shen, J. (Adv. Mater. (Weinheim, Ger.), 2007)

(untitled) - Tong, W.; Gao, C.; Möhwald, H. (Macromol. Rapid Commun., 2006)

(untitled) - Tong, W.; Gao, C.; Möhwald, H. (Polym. Adv. Technol., 2008)

(untitled) - Guo, D.-S.; Liu, Y. (Chem. Soc. Rev., 2012)

(untitled) - Suzuki, I.; Egawa, Y.; Mizukawa, Y.; Hoshi, T.; Anzai, J.-i. (Chem. Commun., 2002)

(untitled) - Crespo-Biel, O.; Dordi, B.; Reinhoudt, D. N.; Huskens, J. (J. Am. Chem. Soc., 2005)

(untitled) - Van der Heyden, A.; Wilczewski, M.; Labbé, P.; Auzély, R. (Chem. Commun., 2006)

(untitled) - Tomatsu, I.; Hashidzume, A.; Harada, A. (Macromol. Rapid Commun., 2006)

(untitled) - Guzmán, E.; Mateos-Maroto, A.; Ruano, M.; Ortega, F.; Rubio, R. G. (Adv. Colloid Interface Sci., 2017)

(untitled) - Qiu, X.; Leporatti, S.; Donath, E.; Möhwald, H. (Langmuir, 2001)

(untitled) - Trubetskoy, V. S.; Loomis, A.; Hagstrom, J. E.; Budker, V. G.; Wolff, J. A. (Nucleic Acids Res., 1999)

(untitled) - Thomas, M. B.; Radhakrishnan, K.; Gnanadhas, D. P.; Chakravortty, D.; Raichur, A. M. (Int. J. Nanomed., 2013)

(untitled) - Wang, Y.; Caruso, F. (Chem. Mater., 2005)

(untitled) - Balabushevich, N. G.; Tiourina, O. P.; Volodkin, D. V.; Larionova, N. I.; Sukhorukov, G. B. (Biomacromolecules, 2003)

(untitled) - Anandhakumar, S.; Nagaraja, V.; Raichur, A. M. (Colloids Surf., B, 2010)

(untitled) - Tripathy, J.; Raichur, A. M. (Colloids Surf., B, 2013)

(untitled) - Köhler, K.; Shchukin, D. G.; Möhwald, H.; Sukhorukov, G. B. (J. Phys. Chem. B, 2005)

(untitled) - Radtchenko, I. L.; Sukhorukov, G. B.; Möhwald, H. (Int. J. Pharm., 2002)

(untitled) - Anandhakumar, S.; Raichur, A. M. (Colloids Surf., B, 2011)

(untitled) - Gao, C.; Donath, E.; Möhwald, H.; Shen, J. (Angew. Chem., Int. Ed., 2002)

(untitled) - Zhao, Q.; Han, B.; Wang, Z.; Gao, C.; Peng, C.; Shen, J. (Nanomedicine (N. Y., NY, U. S.), 2007)

(untitled) - Kurapati, R.; Raichur, A. M. (J. Mater. Chem. B, 2013)

(untitled) - Petrov, A. I.; Volodkin, D. V.; Sukhorukov, G. B. (Biotechnol. Prog., 2005)

(untitled) - Minaeva, O. V.; Brodovskaya, E. P.; Pyataev, M. A.; Gerasimov, M. V.; Zharkov, M. N.; Yurlov, I. A.; Kulikov, O. A.; Kotlyarov, A. A.; Balykova, L. A.; Kokorev, A. V.; Zaborovskiy, A. V.; Pyataev, N. A.; et al. (J. Phys.: Conf. Ser., 2017)

(untitled) - Hu, S.-H.; Tsai, C.-H.; Liao, C.-F.; Liu, D.-M.; Chen, S.-Y. (Langmuir, 2008)

(untitled) - Lee, D.; Rubner, M. F.; Cohen, R. E. (Chem. Mater., 2005)

(untitled) - Wong, M. S.; Cha, J. N.; Choi, K.-S.; Deming, T. J.; Stucky, G. D. (Nano Lett., 2002)

(untitled) - De Geest, B. G.; Skirtach, A. G.; De Beer, T. R.; Sukhorukov, G. B.; Bracke, L.; Baeyens, W. R.; Demeester, J.; De Smedt, S. C. (Macromol. Rapid Commun., 2007)

(untitled) - Bédard, M. F.; Braun, D.; Sukhorukov, G. B.; Skirtach, A. G. (ACS Nano, 2008)

(untitled) - Lehn, J.-M. (Angew. Chem., Int. Ed. Engl., 1990)

(untitled) - Zheng, B.; Wang, F.; Dong, S.; Huang, F. (Chem. Soc. Rev., 2012)

(untitled) - Xu, H.; Stampp, S. P.; Rudkevich, D. M. (Org. Lett., 2003)

(untitled) - Crespo-Biel, O.; Péter, M.; Bruinink, C. M.; Ravoo, B. J.; Reinhoudt, D. N.; Huskens, J. (Chem. – Eur. J., 2005)

(untitled) - Kharlampieva, E.; Sukhishvili, S. A. (Macromolecules, 2003)

(untitled) - Such, G. K.; Johnston, A. P. R.; Liang, K.; Caruso, F. (Prog. Polym. Sci., 2012)

(untitled) - Such, G. K.; Quinn, J. F.; Quinn, A.; Tjipto, E.; Caruso, F. (J. Am. Chem. Soc., 2006)

(untitled) - Jierry, L.; Ben Ameur, N.; Thomann, J.-S.; Frisch, B.; Gonthier, E.; Voegel, J.-C.; Senger, B.; Decher, G.; Felix, O.; Schaaf, P.; Mesini, P.; Boulmedais, F. (Macromolecules, 2010)

(untitled) - Such, G. K.; Tjipto, E.; Postma, A.; Johnston, A. P. R.; Caruso, F. (Nano Lett., 2007)

(untitled) - Ochs, C. J.; Such, G. K.; Städler, B.; Caruso, F. (Biomacromolecules, 2008)

(untitled) - Kinnane, C. R.; Such, G. K.; Antequera-García, G.; Yan, Y.; Dodds, S. J.; Liz-Marzan, L. M.; Caruso, F. (Biomacromolecules, 2009)

(untitled) - Leung, M. K. M.; Such, G. K.; Johnston, A. P. R.; Biswas, D. P.; Zhu, Z.; Yan, Y.; Lutz, J.-F.; Caruso, F. (Small, 2011)

(untitled) - Ochs, C. J.; Such, G. K.; Caruso, F. (Langmuir, 2011)

(untitled) - Yan, Y.; Ochs, C. J.; Such, G. K.; Heath, J. K.; Nice, E. C.; Caruso, F. (Adv. Mater. (Weinheim, Ger.), 2010)

(untitled) - Liang, K.; Such, G. K.; Zhu, Z.; Yan, Y.; Lomas, H.; Caruso, F. (Adv. Mater. (Weinheim, Ger.), 2011)

(untitled) - Connal, L. A.; Kinnane, C. R.; Zelikin, A. N.; Caruso, F. (Chem. Mater., 2009)

(untitled) - Kamphuis, M. M. J.; Johnston, A. P. R.; Such, G. K.; Dam, H. H.; Evans, R. A.; Scott, A. M.; Nice, E. C.; Heath, J. K.; Caruso, F. (J. Am. Chem. Soc., 2010)

(untitled) - Cortez, C.; Tomaskovic-Crook, E.; Johnston, A. P. R.; Radt, B.; Cody, S. H.; Scott, A. M.; Nice, E. C.; Heath, J. K.; Caruso, F. (Adv. Mater. (Weinheim, Ger.), 2006)

(untitled) - Leguen, E.; Chassepot, A.; Decher, G.; Schaaf, P.; Voegel, J.-C.; Jessel, N. (Biomol. Eng., 2007)

(untitled) - Berg, M. C.; Yang, S. Y.; Hammond, P. T.; Rubner, M. F. (Langmuir, 2004)

(untitled) - Picart, C.; Elkaim, R.; Richert, L.; Audoin, F.; Arntz, Y.; Da Silva Cardoso, M.; Schaaf, P.; Voegel, J.-C.; Frisch, B. (Adv. Funct. Mater., 2005)

(untitled) - Chua, P.-H.; Neoh, K.-G.; Kang, E.-T.; Wang, W. (Biomaterials, 2008)

(untitled) - Werner, S.; Huck, O.; Frisch, B.; Vautier, D.; Elkaim, R.; Voegel, J.-C.; Brunel, G.; Tenenbaum, H. (Biomaterials, 2009)

(untitled) - Moya, S.; Donath, E.; Sukhorukov, G. B.; Auch, M.; Bäumler, H.; Lichtenfeld, H.; Möhwald, H. (Macromolecules, 2000)

(untitled) - Qi, W.; Wang, A.; Yang, Y.; Du, M.; Bouchu, M. N.; Boullanger, P.; Li, J. (J. Mater. Chem., 2010)

(untitled) - Krishna, G.; Shutava, T.; Lvov, Y. (Chem. Commun., 2005)

(untitled) - Zhang, F.; Wu, Q.; Chen, Z.-C.; Li, X.; Jiang, X.-M.; Lin, X.-F. (Langmuir, 2006)

(untitled) - Zelikin, A. N.; Li, Q.; Caruso, F. (Angew. Chem., Int. Ed., 2006)

(untitled) - Thompson, M. T.; Berg, M. C.; Tobias, I. S.; Lichter, J. A.; Rubner, M. F.; Van Vliet, K. J. (Biomacromolecules, 2006)

(untitled) - Postma, A.; Yan, Y.; Wang, Y.; Zelikin, A. N.; Tjipto, E.; Caruso, F. (Chem. Mater., 2009)

(untitled) - Yashchenok, A. M.; Bratashov, D. N.; Gorin, D. A.; Lomova, M. V.; Pavlov, A. M.; Sapelkin, A. V.; Shim, B. S.; Khomutov, G. B.; Kotov, N. A.; Sukhorukov, G. B.; Möhwald, H.; Skirtach, A. G. (Adv. Funct. Mater., 2010)

(untitled) - Wang, L.; Wang, N.; Yang, H.; An, Q.; Zeng, T.; Ji, S. (Sep. Purif. Technol., 2018)

(untitled) - Kurapati, R.; Raichur, A. M. (Chem. Commun., 2012)

(untitled) - Kurapati, R.; Raichur, A. M. (Chem. Commun., 2013)

(untitled) - Sui, Z.; Schlenoff, J. B. (Langmuir, 2004)

(untitled) - Sukhorukov, G. B.; Antipov, A. A.; Voigt, A.; Donath, E.; Möhwald, H. (Macromol. Rapid Commun., 2001)

(untitled) - Mauser, T.; Déjugnat, C.; Sukhorukov, G. B. (Macromol. Rapid Commun., 2004)

(untitled) - Mauser, T.; Déjugnat, C.; Sukhorukov, G. B. (J. Phys. Chem. B, 2006)

(untitled) - Imoto, T.; Kida, T.; Matsusaki, M.; Akashi, M. (Macromol. Biosci., 2010)

(untitled) - Cuomo, F.; Lopez, F.; Ceglie, A.; Maiuro, L.; Miguel, M. G.; Lindman, B. (Soft Matter, 2012)

(untitled) - Luo, G.-F.; Xu, X.-D.; Zhang, J.; Yang, J.; Gong, Y.-H.; Lei, Q.; Jia, H.-Z.; Li, C.; Zhuo, R.-X.; Zhang, X.-Z. (ACS Appl. Mater. Interfaces, 2012)

(untitled) - Antipov, A. A.; Sukhorukov, G. B.; Möhwald, H. (Langmuir, 2003)

(untitled) - Guan, Y.; Zhang, Y.; Zhou, T.; Zhou, S. (Soft Matter, 2009)

(untitled) - Gao, C.; Leporatti, S.; Moya, S.; Donath, E.; Möhwald, H. (Chem. – Eur. J., 2003)

(untitled) - Heuvingh, J.; Zappa, M.; Fery, A. (Langmuir, 2005)

(untitled) - Kozlovskaya, V.; Kharlampieva, E.; Mansfield, M. L.; Sukhishvili, S. A. (Chem. Mater., 2006)

(untitled) - Lvov, Y.; Antipov, A. A.; Mamedov, A.; Möhwald, H.; Sukhorukov, G. B. (Nano Lett., 2001)

(untitled) - Caruso, F.; Susha, A. S.; Giersig, M.; Möhwald, H. (Adv. Mater. (Weinheim, Ger.), 1999)

(untitled) - Pastoriza-Santos, I.; Schöler, B.; Caruso, F. (Adv. Funct. Mater., 2001)

(untitled) - Katagiri, K.; Nakamura, M.; Koumoto, K. (ACS Appl. Mater. Interfaces, 2010)

(untitled) - Gorin, D. A.; Portnov, S. A.; Inozemtseva, O. A.; Luklinska, Z.; Yashchenok, A. M.; Pavlov, A. M.; Skirtach, A. G.; Möhwald, H.; Sukhorukov, G. B. (Phys. Chem. Chem. Phys., 2008)

(untitled) - Lu, Z.; Prouty, M. D.; Guo, Z.; Golub, V. O.; Kumar, C. S. S. R.; Lvov, Y. M. (Langmuir, 2005)

(untitled) - Katagiri, K.; Imai, Y.; Koumoto, K. (J. Colloid Interface Sci., 2011)

(untitled) - Angelatos, A. S.; Radt, B.; Caruso, F. (J. Phys. Chem. B, 2005)

(untitled) - Anandhakumar, S.; Vijayalakshmi, S. P.; Jagadeesh, G.; Raichur, A. M. (ACS Appl. Mater. Interfaces, 2011)

(untitled) - Muñoz Javier, A.; del Pino, P.; Bedard, M. F.; Ho, D.; Skirtach, A. G.; Sukhorukov, G. B.; Plank, C.; Parak, W. J. (Langmuir, 2008)

(untitled) - Yi, Q.; Sukhorukov, G. B. (Adv. Colloid Interface Sci., 2014)

(untitled) - Katagiri, K.; Matsuda, A.; Caruso, F. (Macromolecules, 2006)

(untitled) - Koo, H. Y.; Lee, H.-J.; Kim, J. K.; San Choi, W. (J. Mater. Chem., 2010)

(untitled) - Grama, S.; Moleavin, I.-A.; Hodorog-Rusu, A.; Hurduc, N.; Prisacaru, I.; Ibanescu, C. (Mater. Plast. (Bucharest, Rom.), 2013)

(untitled) - Chen, H.; Moore, T.; Qi, B.; Colvin, D. C.; Jelen, E. K.; Hitchcock, D. A.; He, J.; Mefford, O. T.; Gore, J. C.; Alexis, F.; Anker, J. N. (ACS Nano, 2013)

(untitled) - Antipina, M. N.; Sukhorukov, G. B. (Adv. Drug Delivery Rev., 2011)

(untitled) - De Geest, B. G.; Skirtach, A. G.; Mamedov, A. A.; Antipov, A. A.; Kotov, N. A.; De Smedt, S. C.; Sukhorukov, G. B. (Small, 2007)

(untitled) - Shchukin, D. G.; Gorin, D. A.; Möhwald, H. (Langmuir, 2006)

(untitled) - Anandhakumar, S.; Mahalakshmi, V.; Raichur, A. M. (Mater. Sci. Eng., C, 2012)

(untitled) - Kolesnikova, T. A.; Gorin, D. A.; Fernandes, P.; Kessel, S.; Khomutov, G. B.; Fery, A.; Shchukin, D. G.; Möhwald, H. (Adv. Funct. Mater., 2010)

(untitled) - Serpe, M. J.; Yarmey, K. A.; Nolan, C. M.; Lyon, L. A. (Biomacromolecules, 2005)

(untitled) - Serizawa, T.; Matsukuma, D.; Nanameki, K.; Uemura, M.; Kurusu, F.; Akashi, M. (Macromolecules, 2004)

(untitled) - Quinn, J. F.; Caruso, F. (Langmuir, 2004)

(untitled) - Glinel, K.; Sukhorukov, G. B.; Möhwald, H.; Khrenov, V.; Tauer, K. (Macromol. Chem. Phys., 2003)

(untitled) - Mathivanan, N.; Paramasivam, G.; Vergaelen, M.; Rajendran, J.; Hoogenboom, R.; Sundaramurthy, A. (Langmuir, 2019)

(untitled) - Paramasivam, G.; Vergaelen, M.; Ganesh, M. R.; Hoogenboom, R.; Sundaramurthy, A. (J. Mater. Chem. B, 2017)

(untitled) - Sundaramurthy, A.; Vergaelen, M.; Maji, S.; AuzélyVelty, R.; Zhang, Z.; De Geest, B. G.; Hoogenboom, R. (Adv. Healthcare Mater., 2014)

(untitled) - Prevot, M.; Déjugnat, C.; Möhwald, H.; Sukhorukov, G. B. (ChemPhysChem, 2006)

(untitled) - Xu, W.; Ledin, P. A.; Plamper, F. A.; Synatschke, C. V.; Müller, A. H. E.; Tsukruk, V. V. (Macromolecules, 2014)

(untitled) - Timin, A. S.; Gould, D. J.; Sukhorukov, G. B. (Expert Opin. Drug Delivery, 2017)

(untitled) - De Geest, B. G.; De Koker, S.; Sukhorukov, G. B.; Kreft, O.; Parak, W. J.; Skirtach, A. G.; Demeester, J.; De Smedt, S. C.; Hennink, W. E. (Soft Matter, 2009)

(untitled) - Gnanadhas, D. P.; Ben Thomas, M.; Elango, M.; Raichur, A. M.; Chakravortty, D. (J. Antimicrob. Chemother., 2013)

(untitled) - Chen, J.; Ratnayaka, S.; Alford, A.; Kozlovskaya, V.; Liu, F.; Xue, B.; Hoyt, K.; Kharlampieva, E. (ACS Nano, 2017)

(untitled) - Ochs, C. J.; Such, G. K.; Yan, Y.; van Koeverden, M. P.; Caruso, F. (ACS Nano, 2010)

(untitled) - Han, B.; Shen, B.; Wang, Z.; Shi, M.; Li, H.; Peng, C.; Zhao, Q.; Gao, C. (Polym. Adv. Technol., 2008)

(untitled) - Wang, J.; Sun, X.; Mao, W.; Sun, W.; Tang, J.; Sui, M.; Shen, Y.; Gu, Z. (Adv. Mater. (Weinheim, Ger.), 2013)

(untitled) - Huang, S.; Liu, J.; He, Q.; Chen, H.; Cui, J.; Xu, S.; Zhao, Y.; Chen, C.; Wang, L. (Nano Res., 2015)

(untitled) - De Geest, B. G.; Van Camp, W.; Du Prez, F. E.; De Smedt, S. C.; Demeester, J.; Hennink, W. E. (Macromol. Rapid Commun., 2008)

(untitled) - Sexton, A.; Whitney, P. G.; Chong, S.-F.; Zelikin, A. N.; Johnston, A. P. R.; De Rose, R.; Brooks, A. G.; Caruso, F.; Kent, S. J. (ACS Nano, 2009)

(untitled) - De Cock, L. J.; Lenoir, J.; De Koker, S.; Vermeersch, V.; Skirtach, A. G.; Dubruel, P.; Adriaens, E.; Vervaet, C.; Remon, J. P.; De Geest, B. G. (Biomaterials, 2011)

(untitled) - Zyuzin, M. V.; Díez, P.; Goldsmith, M.; Carregal-Romero, S.; Teodosio, C.; Rejman, J.; Feliu, N.; Escudero, A.; Almendral, M. J.; Linne, U.; Peer, D.; Fuentes, M.; et al. (Bioconjugate Chem., 2017)

(untitled) - Ai, H. (Adv. Drug Delivery Rev., 2011)

(untitled) - Chen, H.; Sulejmanovic, D.; Moore, T.; Colvin, D. C.; Qi, B.; Mefford, O. T.; Gore, J. C.; Alexis, F.; Hwu, S.-J.; Anker, J. N. (Chem. Mater., 2014)

(untitled) - Shi, X.; Wang, S. H.; Swanson, S. D.; Ge, S.; Cao, Z.; Van Antwerp, M. E.; Landmark, K. J.; Baker, J. R., Jr (Adv. Mater. (Weinheim, Ger.), 2008)

(untitled) - Yang, P.; Li, D.; Jin, S.; Ding, J.; Guo, J.; Shi, W.; Wang, C. (Biomaterials, 2014)

(untitled) - Yashchenok, A. M.; Jose, J.; Trochet, P.; Sukhorukov, G. B.; Gorin, D. A. (J. Biophotonics, 2016)

(untitled) - Kozlova, A. A.; German, S. V.; Novoselova, M. V.; Demina, P. A.; Atkin, V. S.; Zuev, V. V.; Gorin, D. A. (J. Phys.: Conf. Ser., 2018)

(untitled) - Luo, D.; Poston, R. N.; Gould, D. J.; Sukhorukov, G. B. (Mater. Sci. Eng., C, 2019)

(untitled) - Kreft, O.; Javier, A. M.; Sukhorukov, G. B.; Parak, W. J. (J. Mater. Chem., 2007)

(untitled) - del Mercato, L. L.; Abbasi, A. Z.; Parak, W. J. (Small, 2011)

(untitled) - del Mercato, L. L.; Abbasi, A. Z.; Ochs, M.; Parak, W. J. (ACS Nano, 2011)

(untitled) - RiveraGil, P.; Nazarenus, M.; Ashraf, S.; Parak, W. J. (Small, 2012)

(untitled) - Chinnayelka, S.; McShane, M. J. (Anal. Chem. (Washington, DC, U. S.), 2005)

(untitled) - Srivastava, R.; Jayant, R. D.; Chaudhary, A.; McShane, M. J. (J. Diabetes Sci. Technol., 2011)

(untitled) - Kazakova, L. I.; Shabarchina, L. I.; Anastasova, S.; Pavlov, A. M.; Vadgama, P.; Skirtach, A. G.; Sukhorukov, G. B. (Anal. Bioanal. Chem., 2013)

(untitled) - Palivan, C. G.; Goers, R.; Najer, A.; Zhang, X.; Car, A.; Meier, W. (Chem. Soc. Rev., 2016)

(untitled) - Larrañaga, A.; Lomora, M.; Sarasua, J.-R.; Palivan, C. G.; Pandit, A. (Prog. Mater. Sci., 2017)

(untitled) - Larrañaga, A.; Isa, I. L. M.; Patil, V.; Thamboo, S.; Lomora, M.; Fernández-Yague, M. A.; Sarasua, J.-R.; Palivan, C. G.; Pandit, A. (Acta Biomater., 2018)

(untitled) - Alford, A.; Kozlovskaya, V.; Xue, B.; Gupta, N.; Higgins, W.; Pham-Hua, D.; He, L.; Urban, V. S.; Tse, H. M.; Kharlampieva, E. (Chem. Mater., 2018)

(untitled) - Sharma, V.; Sundaramurthy, A. (ACS Omega, 2019)

(untitled) - Veerabadran, N. G.; Goli, P. L.; StewartClark, S. S.; Lvov, Y. M.; Mills, D. K. (Macromol. Biosci., 2007)

(untitled) - Städler, B.; Price, A. D.; Chandrawati, R.; Hosta-Rigau, L.; Zelikin, A. N.; Caruso, F. (Nanoscale, 2009)

(untitled) - Kerdjoudj, H.; Berthelemy, N.; Boulmedais, F.; Stoltz, J.-F.; Menu, P.; Voegel, J. C. (Soft Matter, 2010)

(untitled) - Zhang, X.; Oulad-Abdelghani, M.; Zelkin, A. N.; Wang, Y.; Haîkel, Y.; Mainard, D.; Voegel, J.-C.; Caruso, F.; Benkirane-Jessel, N. (Biomaterials, 2010)

(untitled) - Becker, A. L.; Orlotti, N. I.; Folini, M.; Cavalieri, F.; Zelikin, A. N.; Johnston, A. P. R.; Zaffaroni, N.; Caruso, F. (ACS Nano, 2011)

(untitled) - Timin, A. S.; Muslimov, A. R.; Lepik, K. V.; Epifanovskaya, O. S.; Shakirova, A. I.; Mock, U.; Riecken, K.; Okilova, M. V.; Sergeev, V. S.; Afanasyev, B. V.; Fehse, B.; Sukhorukov, G. B. (Nanomedicine (N. Y., NY, U. S.), 2018)